Peran Pekerja Sosial dalam Penanganan Lansia Komorbid Covid-19 melalui Program Jiwong Jiga di Purwokerto Wetan: The Role of Social Workers in Handling the Comorbid Elderly with Covid-19 through the Jiwong Jiga Program in Purwokerto Wetan - Siti Aisyah Rizkotul Amalia (AKSIOLOGI: Journal of Community Development, 2025)
This study aims to analyze the role of social workers in assisting elderly individuals with comorbidities through the Jiwong Jiga application in Purwokerto Wetan, as an effort to reduce the spread of Covid-19. Elderly people with comorbid conditions are highly vulnerable to Covid-19 infection, thus requiring community-based approaches for their care and protection. The Jiwong Jiga application, meaning "one person, one guardian," is a local innovation that implements a one-on-one support system to enhance protection for at-risk elderly individuals. This research employed a qualitative descriptive method. Data were collected through in-depth interviews, field observations, and documentation involving five volunteers from the comorbidity team. The findings indicate that the implementation of Jiwong Jiga positively contributed to reducing the risk of Covid-19 transmission among comorbid elderly by enabling direct social interventions. In addition to improving adherence to health protocols, the application also facilitated health monitoring and strengthened the role of social workers in community-based services. The study recommends institutional support and technological integration in future social intervention programs.